(untitled) (The International Research Journal of Management Science, 2017)
This survey examines the extent financial executives use the assumptions and/or inputs of capital structure models generated by academicians in making corporate financing decisions. To gather the views, opinions and perceptions of financial managers regarding corporate capital structure practices a questionnaire survey was conducted. The primary data are used in this study, generated through field study based on questionnaire that obtained from the respondents. One hundred and fifty questionnaires were distributed and eighty six of which were collected and analyzed. Nepalese executives believe that excessive use of debt will increase the cost of fund in its capital structure and they also believe that capital structure evolve as the cumulative outcome of past attempt to time the equity market. Similarly, eighty one per cent of the respondents believe that EFWAMB ratio is one of the important predictive variables of the capital structure choice.